Lipocalin-2 is an inflammatory biomarker associated with metabolic abnormalities in Egyptian obese children - Moushira Erfan Zaki, Hala El-Bassyouni, Eman Youness, Nadi Mohamed (Journal of Applied Pharmaceutical Science, 2015)
Background: The aim of the study was to explore the relationships of lipocalin-2 with metabolic risk factors in obese prepubertal children. Methods: The aim of the study is to examine relationship between serum lipocalin-2 concentrations and metabolic risk factors in 80 obese children and compared with 80 age and sex matched non-obese children controls. Anthropometric and biochemical parameters were measured by standard procedures. Insulin resistance was determined by Homeostasis Model Assessment of Insulin Resistance (HOMA-IR).Results: In the present cross –section study serum lipocalin-2, leptin, insulin, HOMA-IR blood pressure, triglycerides and low-density lipoprotein (LDL-c) and cholesterol were significantly higher in obese children than non-obese, whereas high-density lipoprotein cholesterol (HDL-c) was significantly lower. After adjustment of lipocalin-2 levels for BMI, age and gender, the correlation between serum lipocalin-2 with weight, waist circumference, body fat % and metabolic variables such as fasting insulin; glucose and HOMA-IR triglycerides, cholesterol, LDL-C and HDL-C remained significant. The stepwise multiple regression analysis showed that lipocalin-2 levels were independently associated with LDL-c, total cholesterol, triglycerides and HOMA-IR. Conclusions: lipocalin-2 was significantly elevated in prepubertal obese children and was independently associated with adiposity parameters and its related metabolic complications. The present findings suggest that the measurement of this biomarker may be useful for evaluating metabolic syndrome in Egyptian obese children.
Keywords: Lipocalin-2, metabolic parameters, obesity, Egyptian children.